Pengaruh Kualitas Pelayanan Pusat Mata Nasional Rumah Sakit Mata Cicendo Terhadap Loyalitas Pasien - Zaki Wahyu Mustajab; Uud Wahyudin; Teddy Kurnia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of the service quality of the National Eye Center Cicendo Eye Hospital on outpatient patient loyalty with the Social Exchange Theory proposed by Thibault and Kelley in 1959 as its theoretical foundation. In this study, the researcher employed a correlational method with a quantitative approach. The sample for this study consisted of 96 outpatient patients from the executive installation of the National Eye Center Cicendo Eye Hospital, chosen as respondents through simple random sampling. Subsequently, data analysis involved descriptive analysis and inferential statistica. The research results indicate that simultaneously, the service quality of the National Eye Center at Cicendo Eye Hospital significantly influences the loyalty of outpatient executive installation patients. Furthermore, on a partial level, tangible, reliability, responsiveness, assurance, and empathy in the service quality of the National Eye Center at Cicendo Eye Hospital significantly affect the loyalty of outpatient executive installation patients